2022
DOI: 10.3390/insects13111029
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Elevated CO2 Concentration on Host Adaptability and Chlorantraniliprole Susceptibility in Spodoptera frugiperda

Abstract: Elevated atmospheric carbon dioxide concentrations (eCO2) can affect both herbivorous insects and their host plants. The fall armyworm (FAW), Spodoptera frugiperda, is a highly polyphagous agricultural pest that may attack more than 350 host plant species and has developed resistance to both conventional and novel-action insecticides. However, the effects of eCO2 on host adaptability and insecticide resistance of FAW are unclear. We hypothesized that eCO2 might affect insecticide resistance of FAW by affecting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 58 publications
1
2
0
Order By: Relevance
“…The ramifications of this adaptation extend beyond mere developmental changes to influencing insect life history traits and population dynamics. This is consistent with observations in several lepidopteran species, where eCO 2 exposure reduced larval duration and doubled the population growth rate (Akbar et al., 2016; Lu et al., 2022; Qi et al., 2017; Qian et al., 2017). Thus, eCO 2 concentration may significantly impact MPB biology, ultimately affecting the related ecological and evolutionary processes with their host plants and microbial symbionts (Zavala et al., 2013).…”
Section: Discussionsupporting
confidence: 91%
“…The ramifications of this adaptation extend beyond mere developmental changes to influencing insect life history traits and population dynamics. This is consistent with observations in several lepidopteran species, where eCO 2 exposure reduced larval duration and doubled the population growth rate (Akbar et al., 2016; Lu et al., 2022; Qi et al., 2017; Qian et al., 2017). Thus, eCO 2 concentration may significantly impact MPB biology, ultimately affecting the related ecological and evolutionary processes with their host plants and microbial symbionts (Zavala et al., 2013).…”
Section: Discussionsupporting
confidence: 91%
“…The excess of 1000 third-instar S. frugiperda larvae were tested at the LC 50 concentration of chlorantraniliprole via the leaf impregnation method adapted from a previous study . After 48 h postexposure, surviving larvae were grouped for further selection with chlorantraniliprole.…”
Section: Methodsmentioning
confidence: 99%
“…The excess of 1000 thirdinstar S. frugiperda larvae were tested at the LC 50 concentration of chlorantraniliprole via the leaf impregnation method adapted from a previous study. 28 After 48 h postexposure, surviving larvae were grouped for further selection with chlorantraniliprole. Through ten successive selections, chlorantraniliprole-resistant (Ch-R) and chlorantraniliprole-susceptible (Ch-Sus) strains were developed to use as controls.…”
Section: Selection Of a Chlorantraniliprole-resistant S Frugiperda St...mentioning
confidence: 99%
“…Li et al [40] showed that CarE, GST, and CYP450 activity in F. occidentalis increase significantly after treatment with an LC 25 dose of spinetoram, while the activity of AChE decreases. Detoxification enzymes play essential roles in the survival of insects exposed to adverse environments [41][42][43][44]. Therefore, higher detoxifying enzyme activity indicates the involvement of those enzymes in insecticide stress, thereby changing the insecticide susceptibility in insects.…”
Section: Introductionmentioning
confidence: 99%